Aged to Perfection: How Company Age Moderates the Relationship Between Size and Financial Reporting Timeliness - Neng Asiah; Wahyudin Eka Surya (Jurnal Akuntansi Bisnis Pelita Bangsa, 2025)
This study examines the influence of company size and company age on financial reporting timeliness and explores whether company age moderates this relationship. Data were obtained from 22 property and real estate companies listed on the Indonesia Stock Exchange during 2022-2024. Descriptive statistics and moderated regression analysis were applied to evaluate the relationships between firm characteristics and audit delay. The findings indicate that larger and older companies report more promptly, suggesting that organizational scale and maturity enhance reporting efficiency. Furthermore, company age strengthens the positive impact of firm size on reporting timeliness, implying that mature firms can better manage the complexity associated with larger operations. These results support the Resource-Based View and Organizational Life Cycle Theory, highlighting how resources and experience jointly improve financial reporting discipline. The study contributes to developing corporate governance and reporting efficiency literature in emerging markets.